Late angiotensin II receptor blockade in progressive rat mesangioproliferative glomerulonephritis: new insights into mechanisms. Issue 5 (5th March 2013) - Villa, Luigi; Boor, Peter; Konieczny, Andrzej; Kunter, Uta; van Roeyen, Claudia RC; Denecke, Bernd; Gan, Lin; Neusser, Matthias A; Cohen, Clemens D; ,; Eitner, Frank; Scholl, Thomas; et al.
Abstract Mesangioproliferative glomerulonephritis is the most common nephritis worldwide. We examined the effects of low‐ and high‐dose telmisartan, an angiotensin II receptor blocker, in rats with progressive anti‐Thy1.1 mesangioproliferative glomerulonephritis in a clinically relevant situation of established renal damage. Uninephrectomized nephritic rats were randomized on day 28 to remain untreated (control treatment; CT), or to receive low‐ (0.1 mg/kg/day, LT) or high‐dose telmisartan (10 mg/kg/day, HT), hydrochlorothiazide + hydralazine (8 + 32 mg/kg/day, HCT + H), or atenolol (100 mg/kg/day, AT). CT and LT rats were hypertensive, whereas HT, HCT + H and AT treatment normalized blood pressures. On day 131, despite similar blood lowering effects, only HT, but not AT or HCT + H, prevented loss of renal function and reduced proteinuria compared to CT. Only HT potently ameliorated glomerulosclerosis, tubulointerstitial damage, cortical matrix deposition, podocyte damage and macrophage infiltration. HT reduced cortical expression of platelet derived growth factor receptor‐α and ‐β as well as transforming growth factor‐β1. LT exhibited minor but significant efficacy even in the absence of antihypertensive effects. Transcript array analyses revealed a four‐fold down‐regulation of renal cortical chemokine (C–C motif) receptor 6 (CCR6) mRNA by HT, which was confirmed at the protein level. Silencing of CCR6 did not alter podocyte function in vitro, thus indicating a predominant role in the tubulo‐interstitium. In human kidney biopsies, CCR6 mRNA and mRNA of its ligand chemokine (C–C motif) ligand 20 was up‐regulated in patients with progressive IgA nephropathy compared to stable disease. Thus, delayed treatment with high‐dose telmisartan exerted a pronounced benefit in progressive mesangioproliferative glomerulonephritis, which extended beyond that of equivalent blood pressure lowering. We identified down‐regulation of platelet‐derived growth factor receptors and CCR6 as potential mediators of telmisartan‐related renoprotection. CCR6 may also regulate the renal outcome in human mesangioprolfierative glomerulonephritis. Copyright © 2012 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.